Perinatal mortality in adolescent mothers. Perinatal Maternal Institute - Acosta Chávez, Manuel (2022)
Perinatal deaths that did take place at the Institute Materno Perinatal from jannuary 1999 to October 2000, were studied. During this time 37,852 babies wereborn, of wich 36,995 were liveborns, 395 stillborns and 462 died during the first seven days of life.In order to study Perintal mortality I related to mothers age, these were groupedos: Yamger than 19, 20 to 25, 26 to 30, 31 to 36 and older than 36 years of age.Perinatal mortality rate vas 22.64; too high for western world levels but lower than the one registered at national level. Perinatal mortality rate in adolescents is lower than the one found in other age groups. The rate for numbers of liveborns was: 18.70 per 1000 in the 26 to 30 age group, 37.28 in the 31 to 36 age group, and 38.38 for women older than 36 years of age these data shows that perinatal mortality I, increased withage of the mother.Perinatal mortality I related to their fetal and early neonatal components, sociobiological factors, diag. nosis, different types of placenta ad adnexae pathologies, were stadied.The fallowing factors related to perinatal deaths in adolescents aged 14, 14 to 16 and 17 to 19 years, as marital status, weight, height, fetal heart rate on admission, time when fetal deaths took place, admission diagnosis of fetal death, early neonatal deaths and pathological study of placenta and adnexae, were described.